Percutaneous transseptal transcatheter mitral valve-in-valve replacement for degenerated mitral bioprosthesis: The first experience in Japan. Issue 1 (January 2021) - Ueno, Hiroshi; Hida, Yuki; Ueno, Yohei; Tanaka, Shuhei; Ushijima, Ryuichi; Sobajima, Mitsuo; Fukuda, Nobuyuki; Imamura, Teruhiko; Kameyama, Akiyo; Komiya, Ryosuke; Ito, Hisakatsu; Yokoyama, Shigeki; et al.
Abstract: A 76-year-old woman had received surgical mitral valve replacement with Magna Mitral Ease (Edwards Lifesciences, Irvine, CA, USA) 25 mm for functional severe mitral regurgitation 6 years previously. She presented recurrence of heart failure due to severe stenotic and moderate regurgitant degeneration of the implanted mitral bioprosthesis. Considering her comorbidities and left ventricular systolic dysfunction, our heart valve team eventually decided to perform percutaneous transseptal transcatheter mitral valve-in-valve replacement instead of surgical redo mitral valve replacement, using a 26 mm SAPIEN 3 valve (Edwards Lifesciences) via trans-femoral approach. Post-procedural course was uneventful and she was discharged on post-procedural day 2. This is, to the best of our knowledge, the first case of successful percutaneous transseptal transcatheter mitral valve-in-valve replacement in Japan. Further large-scale prospective studies are warranted to validate its long-term safety and efficacy, particularly by comparing with the redo surgery. <Learning objective: We experienced an off-label transseptal mitral valve-in-valve replacement using SAPIEN 3 to treat degenerative mitral bioprosthesis for the first time in Japan. Although further large-scale prospective studies are warranted, this procedure should be a promising therapeutic alternative to conventional redo-surgery, particularly for elderly patients with multiple comorbidities.>